Pengaruh Faktor Fundamental Terhadap Harga Saham Pada PT. Telkom Indonesia (Persero) Tbk dan PT. Smartfren Telecom Tbk (Periode 2015 – 2019) - Arifin, Agus; Fadhillah, Muhammad Haris (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This research aims to examine the effect of fundamental factors of Current Ratio (CR), Earning Per Share (EPS), Debt To Equity Ratio (DER), and Turnover Total Assets (TATO)on Stock Price in PT. Telkom Indonesia (Persero) Tbk (TLKM) and PT Smartfren TelecomTbk (FREN) from 2015 until 2019. This research used multiple linear regression with F testand t test using IBM SPSS 26.0. The results show that CR, EPS, DER, and TATOsimultaneously or partially affected the stock price of TLKM and FREN.